Common Chinese Materia Medica Volume 7 - Ye, Huagu; Li, Chuyuan; Ye, Wencai; Zeng, Feiyan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This seventh volume describes 247 species of 9 families of medicinal plants, which are commonly used in Chinese medicine. The most important species are Adina rubella, Gardenia jasminoides, Hedyotis diffusa, Morinda officinalis, Rubia cordifolia, Uncaria hirsuta, Uncaria macrophylla, Uncaria rhynchophylla, Uncaria sessilifructus, Uncaria sinensis of Rubiaceae; Lonicera confusa, Lonicera hypoglauca, Lonicera macranthoides, Lonicera japonica of Caprifoliaceae; Patrinia scabiosaefolia, Patrinia villosa, Nardostachys jatamansi of Valerianaceae; Dipsacus asperoides of Dipsacaceae; Arctium lappa, Artemisia annua, Artemisia argyi, Artemisia capillaris, Artemisia scoparia, Atractylodes lancea, Atractylodes macrocephala, Dendranthema indicum, Dendranthema morifolium, Eupatorium chinense, Eupatorium fortunei, Inula helenium, Saussurea costus, Saussurea involucrata, Senecio scandens, Serratula chinensis, Siegesbeckia orientalis, Solidago decurrens, Taraxacum mongolicum, Tussilago farfara$1!+5(BXanthium sibiricum of Compositae; Gentiana crassicaulis, Gentiana manshurica, Gentiana rigescens, Gentiana scabra, Swertia pseudochinensis of Valerianaceae; Lysimachia christinae of Primulaceae and Plantago asiatica of Plantaginaceae. In each specie, it introduces the scientific names, medicinal names, morphologies, habitats, distributions, acquisition and processing methods of these medicinal plants, the content of medicinal properties, therapeutic effects, usage and dosage of these medicinal plants, and attaches unedited color pictures and pictures of part herbal medicines of each species. This book series has 10 volumes in total, which covers over 2000 kinds of Chinese medicines that are commonly used. These volumes not only introduce the efficacy function and some prescriptions of the medicines, but also introduce the biological characteristics of them in detail with clear photos of the habitats, so that readers can identify them in the field. Apart from the growing environment, the books expound the distribution areas and other information to facilitate researches and other applications. The volumes are targeted at readers of general interests and it is also of high referential value for scientific researcher and teachers. It can be used as a guide to researchers, clinical doctors, and students in the department of pharmaceutics and traditional Chinese medicine.s
Adina rubella -- Gardenia jasminoides -- Hedyotis diffusa -- Morinda officinalis -- Rubia cordifolia -- Uncaria hirsuta -- Uncaria macrophylla -- Uncaria rhynchophylla -- Uncaria sessilifructus -- Uncaria sinensis of Rubiaceae; Lonicera confusa -- Lonicera hypoglauca -- Lonicera macranthoides -- Lonicera japonica of Caprifoliaceae; Patrinia scabiosaefolia -- Patrinia villosa -- Nardostachys jatamansi of Valerianaceae; Dipsacus asperoides of Dipsacaceae; Arctium lappa -- Artemisia annua -- Artemisia argyi -- Artemisia capillaris -- Artemisia scoparia -- Atractylodes lancea -- Atractylodes macrocephala -- Dendranthema indicum -- Dendranthema morifolium -- Eupatorium chinense -- Eupatorium fortunei -- Inula helenium -- Saussurea costus -- Saussurea involucrata -- Senecio scandens -- Serratula chinensis -- Siegesbeckia orientalis -- Solidago decurrens -- Taraxacum mongolicum -- Tussilago farfara$1!+5(BXanthium sibiricum of Compositae; Gentiana crassicaulis -- Gentiana manshurica -- Gentiana rigescens -- Gentiana scabra -- Swertia pseudochinensis of Valerianaceae; Lysimachia christinae of Primulaceae and Plantago asiatica of Plantaginaceae.s
Keywords: Pharmacy; Medicine; Plants$1 (BEvolution.s; Pharmacy; Clinical Medicine; Plant Evolution; Materia Medica